Utilization of Historical Film as a History Learning Media to Increase History Awareness in SMA Negeri 50 Jakarta - Arlyan Merryasni; Umasih Umasih; Sarkadi Sarkadi (STAI Miftahul Ula Nganjuk, 2022)
The purpose of this study is to increase students' historical awareness through the application of film media in history learning. This research will be conducted with the main focus on the use of historical-themed commercial films in increasing historical awareness at SMAN 50 JAKARTA. The research will be conducted from February to May 2022. The method used in this research is descriptive qualitative. The data analysis technique used is descriptive qualitative through three paths, namely (1) data reduction, (2) data presentation, and (3) drawing conclusions. Data collection methods were carried out through in-depth interviews, participatory observations, documentary materials, as well as new methods such as visual methods and internet search methods. Informants in this study were history teachers at SMA NEGERI 50 JAKARTA and students, secondary data contained in learning tools. The results of this study become recommendations for teachers so that students have the ability to process information so that history learning is more meaningful. This shows that the application of film media to increase students' History Awareness is one way that can be used in learning history at school. Historical films are used as teaching media to really help history teachers to attract students' interest. The teacher uses historical films as the first step in starting new material so that students have an overview of the material to be discussed. The use of historical films for students is considered much more enjoyable because the film has a storyline and makes it easier for students to understand the chronology of an event.